2018
DOI: 10.1016/j.jchf.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type 2 Diabetes and All-Cause Hospitalization and Mortality in the UK General Heart Failure Population

Abstract: In the general HF population, T2D stratified by glycemic control and drug treatments showed differential risk associations. Routine measures of dynamic diabetes status provide important prognostic indication of poor outcomes in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 25 publications
2
52
0
7
Order By: Relevance
“…Conversely, patients requiring insulin demonstrated a higher risk of all outcomes compared with individuals without T2DM as well as those on oral glucose‐lowering medications. This most likely reflects a longer duration of T2DM, poorer glycaemic control, and greater burden of unaccounted microvascular complications and hypoglycaemia, which, alone, or in combination, could have augmented the risk of HF and mortality among insulin‐treated patients . A recent report from a Swedish nationwide cohort study demonstrated a higher risk of mortality, HF, MI and ischaemic stroke in insulin‐treated AF patients, adding to a previous report of increased risk of thromboembolism among insulin‐treated participants of the PREFER in AF Registry (European Prevention of thromboembolic events‐European Registry in Atrial Fibrillation) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, patients requiring insulin demonstrated a higher risk of all outcomes compared with individuals without T2DM as well as those on oral glucose‐lowering medications. This most likely reflects a longer duration of T2DM, poorer glycaemic control, and greater burden of unaccounted microvascular complications and hypoglycaemia, which, alone, or in combination, could have augmented the risk of HF and mortality among insulin‐treated patients . A recent report from a Swedish nationwide cohort study demonstrated a higher risk of mortality, HF, MI and ischaemic stroke in insulin‐treated AF patients, adding to a previous report of increased risk of thromboembolism among insulin‐treated participants of the PREFER in AF Registry (European Prevention of thromboembolic events‐European Registry in Atrial Fibrillation) .…”
Section: Discussionmentioning
confidence: 94%
“…This most likely reflects a longer duration of T2DM, poorer glycaemic control, and greater burden of unaccounted microvascular complications and hypoglycaemia, which, alone, or in combination, could have augmented the risk of HF and mortality among insulin-treated patients. 46,47 A recent report from a Swedish nationwide cohort study demonstrated a higher risk of mortality, HF, MI and ischaemic stroke in insulin-treated AF patients, 7 adding to a previous report of increased risk of thromboembolism among insulin-treated participants of the PREFER in AF Registry (European Prevention of thromboembolic events-European Registry in Atrial Fibrillation). 48 Collectively, these findings suggest that T2DM requiring insulin might identify a vulnerable group of AF patients, who merit meticulous anticoagulation and, possibly, consideration of glucose-lowering therapies with a proven benefit for HF risk reduction (e.g.…”
Section: The Association Between Type 2 Diabetes Treatment and Outcomesmentioning
confidence: 98%
“…150 Insulin-related hypoglycaemia may also activate the sympathetic nervous system and promote arrhythmogenesis. 151 Accordingly, insulin use has been accompanied by an increased risk for AF 152,153 and HF 154,155 and an enhanced likelihood of poor outcomes (including stroke) in patients with established HFpEF. 73,156,157…”
Section: Effects Of Antihyperglycaemic Drugs In Patients With a Metabmentioning
confidence: 99%
“…Most data suggest that mortality risk in patients with HF is lowest with moderate glycaemic control (i.e. HbA 1c levels 7.0–7.9%) . Therefore, the 2016 European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of HF stipulate that adequate glycaemic control should be achieved gradually and leniently, with agents shown to be safe and effective .…”
Section: Introductionmentioning
confidence: 99%
“…HbA 1c levels 7.0-7.9%). [10][11][12][13][14] Therefore, the 2016 European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of HF stipulate that adequate glycaemic control should be achieved gradually and leniently, with agents shown to be safe and effective. 15 A holistic approach to T2DM management in HF should also include blood pressure, body weight, and lipid control, while avoiding hypoglycaemia, which is associated with a greater risk of death 16 and may be a cause of increased mortality in diabetic patients with HF on insulin therapy.…”
Section: Introductionmentioning
confidence: 99%